Meta-analysis of the influence of different element contents on selecting the prediction model of gray cast iron's elastic modulus. Issue 1 (1st December 2022) - Hu, Chunyang; Liu, Qi; Du, Yutong; Zhang, Junjia; Jiang, Ou; Che, Fei
Abstract : In order to explore the influence of different element contents on selecting the prediction model of gray cast iron's modulus, we apply Meta-analysis to retrieve Chinese journals related to gray cast iron and elastic modulus and adopt fixed effect models to evaluate and analyze the introducedδ value, hoping to provide theoretical basis for prediction model of elastic modulus. According to the analytical results: (1) When the silicon content is relatively low, the model E0 =101.32+2.51Si/C is suggested for prediction. (2) When the carbon content is relatively low, the model E0 =313.175-49.014C-14.082Si is suggested for prediction. (3) When the two elements are both relatively low, Si/C value-based judgment needs to be made that the model E0 =101.32+2.51Si/C is suggested when the value is relatively low. (4) When either the silicon content or the CE (carbon equivalent) is relatively low, the model E0 =194.55-27.85CE+58.2Si/C or the model with three variables-E0 =20.527-0.021Si/C+59.2841Si+0.004CE is suggested for prediction. (5) When some of the above cases exist simultaneously, the preferable model selection should be considered in the following order of priority: C=Si>Si/C>CE>S.